1996
DOI: 10.1037/0033-2909.119.3.448
|View full text |Cite
|
Sign up to set email alerts
|

Empirical research on religion and psychotherapeutic processes and outcomes: A 10-year review and research prospectus.

Abstract: A decade of research on religion and counseling, consisting of 148 empirical articles, was reviewed. Methodological sophistication, poor a decade ago, has approached current secular standards, except in outcome research. Religious people cannot be assumed to be mentally unhealthy. Nonreligious and religious counselors share most counseling-relevant values but differ in the value they place on religion. Those religious differences affect clinical judgment and behavior, especially with religious clients. Religio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
277
0
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(300 citation statements)
references
References 229 publications
12
277
0
8
Order By: Relevance
“…Examples of interventions that blend health and spiritual components are already beginning to emerge in the literature, with promising results (e.g. McCullough, 1999;Propst, Ostrom, Watkins, Dean, & Mashburn, 1992;Worthington, Kurusu, McCullough, & Sandage, 1996). In sum, this study of religious coping has helped us not only understand the ways religion expresses itself in the midst of medical illness, it has helped set the stage for efforts to integrate religion and spirituality more fully into clinical practice.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…Examples of interventions that blend health and spiritual components are already beginning to emerge in the literature, with promising results (e.g. McCullough, 1999;Propst, Ostrom, Watkins, Dean, & Mashburn, 1992;Worthington, Kurusu, McCullough, & Sandage, 1996). In sum, this study of religious coping has helped us not only understand the ways religion expresses itself in the midst of medical illness, it has helped set the stage for efforts to integrate religion and spirituality more fully into clinical practice.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…Although religious doctrine and communities can mandate forgiveness, individuals vary in the way in which they observe such expectations (Girard & Mullet, 1997;Worthington, Sharp, Lerner, & Sharp, 2006). In fact, Worthington, Kurusu, McCullough, and Sandage (1996) have suggested that only those individuals who score higher than one standard deviation above the mean on religious variables tends to make meaning of the world through the lens of re-ligion. Thus, although participants might have identified as being Muslim and though the Qur'an speaks to the importance of forgiveness, participants likely differ in the way in which Islam influences forgiveness attitudes.…”
Section: Discussion Of Main Resultsmentioning
confidence: 99%
“…Ostatnią waĪną cechą kwestionariusza jest praktyczny powód jego powstania. Został on stworzony do pomiaru religijnoĞci klientów i pacjentów w procesie psychoterapii ze wzglĊdu na istotny wpływ przekonaĔ religijnych i tolerancji na relacje z terapeutą oraz oczekiwania wzglĊdem terapii (Worthington, 1988;Worthington, Kurusu, McCollough i Sandage, 1996). Fakt ten wpływa znacząco na konstrukcjĊ narzĊdzia; dotyczy ono przede wszystkim skutków, jakie religijnoĞü wywiera na funkcjonowanie w Ğwieckich sytuacjach.…”
Section: Wprowadzenieunclassified